PENGARUH KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI BANTEN PADA TAHUN 2019-2023 - Ulis Sintia; romenah (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of regional tax and regional levy contributions on economic growth in Banten Province in 2019-2023. This type of research is quantitative research. The dependent variable used in this study is economic growth and the independent variable in this study is the contribution of regional taxes and regional levies. The research used in this study is the districts/cities in BPS (Central Statistics Agency). Data analysis used is panel data regression analysis. The cross-section data in this study are 8 districts/cities in Banten Province and the time series data in this study are 2019 to 2023 using the saturated sample method. All data used are entered into a computer statistics program, namely E-Views 12 for testing. The results of the study can be concluded that the contribution of regional taxes and regional levies simultaneously does not have a significant effect on economic growth in Banten Province 2019-2023. The results of the study show that the contribution of regional taxes and regional levies significantly partially affects economic growth